Faktor-faktor yang berhubungan dengan perilaku Pencegahan kanker serviks pada wanita usia subur - Dwikha - Gustiana; Yulia Irvani Dewi; Sofiana - Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research aims to determine the influence factors of cervical cancer prevention behavior of childbearing woman. Methodology on this research was a survey design with cross sectional approach. The sample in this research were 99 respondents who live in Rejosari with snowball sampling technique. Measuring instruments used was a questionnaire. The analysis used was univariate and bivariate analysis using Chi-Square test and Fisher Exact test. The results showed there were relations between knowledge (ρ=0.045) and social support (ρ=0.000) toward behavior cervical cancer prevention. While age (ρ=0.306), education (ρ=1.000), and economy (ρ=0.561) there were not the relations toward behavior cervical cancer prevention. Based on the results of this research, it is recommended for health care institutions especially for public health center staff to increased a health education of cervical cancer prevention and extend a health promotion target. Keyword: Cervical cancer, childbearing woman, prevention behavior